Dry needling as a therapeutic alternative in the treatment of chronic headaches - Rubén Martínez, Hugo; Martinez, Cesar (International Journal of Neurology, 2024)
Headaches were one of the most prevalent neurological conditions worldwide and a frequent reason for consulting health services, due to their negative impact on the quality of life, work performance and emotional well-being of those who suffered from them. The purpose of this study was to analyse the clinical characteristics of headaches and examine the role of dry needling as a therapeutic alternative within the kinesiological approach, with special emphasis on tension headaches and other headaches of musculoskeletal origin. The main types of headaches were described according to the classification of the International Headache Society, highlighting migraine and tension headaches due to their high prevalence and association with factors such as stress, muscle tension, and postural overload. The pathophysiological mechanisms involved were also addressed, including genetic predisposition, central sensitisation, and the influence of emotional and environmental triggers. Dry needling was analysed as a technique based on neurophysiological and myofascial models, aimed at deactivating trigger points and modulating nociceptive afferents. Its effects at the peripheral and central levels were demonstrated, such as decreased referred pain, reduced muscle sensitivity, and improved motor function. The evidence reviewed showed that the application of dry needling was associated with significant reductions in pain intensity and frequency, as well as relevant improvements in patients' quality of life. In conclusion, dry needling was presented as an effective and promising intervention for the comprehensive management of chronic headaches, justifying its inclusion in multidisciplinary therapeutic strategies.